Pendidikan yang Memerdekakan dalam Perspektif Ki Hajar Dewantara dan Implikasinya untuk Pendidikan SMP - Ahmad Muamar Zaenul Hakim; Elis Nursari; Rini Rosmiati; Ricky Yoseptry (STKIP PGRI SITUBONDO, 2025)
This study is grounded in the thought of Ki Hajar Dewantara, who viewed education as an effort to liberate human beings—that is, to shape learners so that they can develop in accordance with their natural potential, possess noble character, and become independent individuals without losing their human values. This study aims to: (1) describe the concept of liberating education according to Ki Hajar Dewantara; (2) analyze the relevance of this concept to the needs of 21st-century education; and (3) examine the implications of Ki Hajar Dewantara’s ideas for the education system at the junior high school level, including aspects of curriculum, learning, school management, and institutional culture. The method employed is library research using a descriptive qualitative approach. Data sources include the original works of Ki Hajar Dewantara, academic studies on character education and humanistic education, as well as national education policy documents such as the Merdeka Curriculum and the Pancasila Student Profile. The data were analyzed through data reduction, categorization, interpretation, and thematic conclusion drawing. The findings indicate that Ki Hajar Dewantara’s concept of liberating education emphasizes three main principles: (1) exemplary leadership (ing ngarso sung tulodo), (2) empowerment and motivation (ing madya mangun karso), and (3) encouragement of independence (tut wuri handayani). These three principles have strong implications for the junior high school education system. In terms of curriculum, there is a need to strengthen flexibility, learning differentiation, and character development. In the learning process, teachers need to act as mentors who guide students through dialogical, reflective, and experiential approaches. In terms of school management, a democratic and participatory school culture is required, positioning students as active subjects of learning. This study concludes that the implementation of liberating education at the junior high school level can strengthen a humanistic educational ecosystem that is relevant to the developmental needs of learners.